30.6k views
3 votes
Which of the following cannot be solved using the quadratic formula?

Which of the following cannot be solved using the quadratic formula?-example-1

2 Answers

6 votes

Answer:

A.
-3x^(2)-x+3=-3x^(2)

Explanation:

We know that,

The quadratic formula is used to find the solution of a quadratic equation
ax^(2)+bx+c=0 i.e. an equation of degree 2.

Now, in option A, we have,


-3x^(2)-x+3=-3x^(2) i.e.
-x+3=-3x^(2)+3x^(2) i.e.
-x+3=0

So, the final equation is not a quadratic equation but it is a linear equation.

Hence, for this equation, we cannot use the quadratic formula.

User ManicMonkOnMac
by
4.3k points
3 votes

Answer:

Option A is correct, i.e. -3x² -x +3 = -3x²

Explanation:

We can rearrange the terms, and combine like terms to get each equation in standard form of quadratic equation like ax²+bx+c=0.

It must have degree 2 to be solved using quadratic formula.

Option A: -3x² -x +3 = -3x²

Rearranging the terms:-

3x² -3x² -x +3 = 0

Combining like terms:-

0 -x +3 = 0

-x +3 = 0

This is linear equation with degree 1 and can be solved without quadratic formula.

Hence, option A is correct, i.e. -3x² -x +3 = -3x²

User Jordan Carter
by
6.0k points